Differential Pulse Voltammetry Technique Using Ferrocene-Modified Carbon Paste Electrodes for Determination of Pb(II) In Kepok Banana - Irdhawati Irdhawati; Feby Silvia; Emmy Sahara; Nur Alisyah Gani (Syarif Hidayatullah State Islamic University, 2020)
The voltammetry method is a field of electrochemistry that measures electric current at a certain potential, which can be used to determine the concentration of inorganic and organic compounds that can be oxidized or reduced. In this research, the differential pulse voltammetry (DPV) technique has been used to determine the content of Pb(II). The carbon paste electrode (CPE) and ferrocene-modified carbon paste electrode (CPE-Fc) were used as working electrodes. This study aims to improve the sensitivity of Pb(II) measurement. Two parameters were optimized were ferrocene composition and scan rate. The validation parameters involved the linear concentration range, detection limit, quantization limit, precision and accuracy. The optimum ferrocene composition was found at 6%, and scan rate was 15 mV/s using CPE, increase to 20 mV/s using CPE-Fc. The validation results showed the linearity using CPE-Fc wider than CPE at the peak potential of 0.515 V. The detection and quantization limit values using CPE were 0.1551 µg/L and 0.1556 µg/L, and down to 0.1089 µg/L and 0.1090 µg/L using CPE-Fc. The precision determination for both of CPE and CPE-Fc had good results, indicated by the Horwitz ratio less than two. Percentage of recovery using CPE-Fc of 85.59 8.18%. CPE-Fc at the optimum measurement conditions was used to determine the levels of Pb(II) in kepok banana, and the result was obtained 4.4306 0.0009 mg/kg. The level of Pb content was found to exceed the established threshold based on Standard National Indonesia (ISN) No. 7387:2009 which is 0.5 mg/kg.